Bilingual ESL Education: Program Evaluation Report. - Texas Education Agency, Austin; Texas Education Agency, Austin ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
The statewide overview of Texas bilingual and English-as-a-Second-Language (ESL) programs for limited-English-speaking public school students reports results of a survey concerning program and student characteristics and successful instructional practices. Data for bilingual and ESL programs are considered separately. Student characteristics studied include eligibility for free or reduced-price lunches, mobility within and among districts, English reading level, previous schooling, native language use in the classroom, attendance patterns, participation in extracurricular activities, the need for intervention as perceived by staff, and the students' success or perceived success in the program. Exit and promotion rates and the need for remedial instruction are also examined. Instructional program data investigated include campus instructional strategies, percentages of students enrolled in other compensatory programs, use of reduced- or modified-content classes, class size, teacher language use in the classroom, and student promotion and success. Other variables examined include teacher qualifications and experience, parent involvement, student performance on objective measures, student achievement gains, and actual or perceived success. Appended materials include the questionnaire, coding information, evaluation requirements, and a brief comparison of the bilingual and ESL studies. (MSE)
Availability: Publications Distribution Office, Texas Education Agency, 1701 North Congress Avenue, Austin, TX 78701-1494 ($3.50).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education Programs; Classroom Research; Educational Strategies; Elementary Secondary Education; English (Second Language); Limited English Speaking; Predictor Variables; Program Design; Program Effectiveness; Public Schools; Remedial Instruction; Second Language Programs; State Programs; State Surveys; Student Characteristics; Student Promotion; Texas; Reports, Research; Tests/Questionnaires.